Positive electrode active material, method of preparing same, and positive electrode and rechargeable lithium battery including same

By forming Al, Zr and Mg coatings on the surface of lithium nickel-manganese composite oxide positive electrode active substances, the problem of shortage of cobalt supply in lithium battery positive electrode active substances is solved, and high energy density and long cycle life are achieved Effect.

CN119447220APending Publication Date: 2025-02-14SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411064772.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-08-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The active substances of existing lithium batteries contain rare metal cobalt, which is short of supply and high cost, making it difficult to meet the needs of high energy density and long cycle life.

Method used

A positive electrode active substance based on lithium nickel-manganese composite oxide is used, and a coating of Al, Zr and Mg is formed on its surface, so that the structural stability and electrochemical properties of the material are improved through a heat treatment process.

Benefits of technology

High capacity, long cycle life and improved high voltage and high temperature characteristics are achieved, reducing the amount of gas generated under high voltage and high temperature conditions and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447220A_ABST
    Figure CN119447220A_ABST
Patent Text Reader

Abstract

The present application discloses a positive electrode active material, a method of preparing the same, and a positive electrode and a rechargeable lithium battery including the same, the positive electrode active material including: a core particle including a lithium nickel manganese-based composite oxide in which a nickel content is greater than or equal to about 60 mol% based on a total amount of a metal other than lithium of 100 mol% in the lithium nickel manganese-based composite oxide; and a coating layer disposed on a surface of the core particle and including Al, Zr, and Mg.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0101766 filed in the Korean Intellectual Property Office on August 3, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Disclosed are a positive electrode active material, a preparation method thereof, and a positive electrode and a rechargeable lithium battery including the same. Background Art

[0004] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) or electric vehicles have used rechargeable lithium batteries with high energy density and easy portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with high energy density as driving power sources or energy storage power sources for hybrid vehicles or electric vehicles.

[0005] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for these applications. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand for rechargeable lithium batteries with large size, high capacity or high energy density has increased recently, the supply of positive electrode active materials containing rare metal cobalt is expected to be in serious shortage. In other words, since cobalt is expensive and there is a lack of remaining reserves, it is necessary to develop positive electrode active materials that exclude cobalt or use cobalt in a reduced amount. Summary of the invention

[0006] Some embodiments provide: a positive electrode active material, a method for preparing a positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery, wherein the positive electrode active material includes a lithium nickel manganese composite oxide, ensures economic feasibility, high capacity and long cycle life characteristics, and exhibits improved high voltage characteristics and high temperature characteristics.

[0007] In some embodiments, the positive electrode active material includes: a core particle, which includes a lithium nickel manganese composite oxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total amount of metals other than lithium in the lithium nickel manganese composite oxide; and a coating disposed on the surface of the core particle and including Al, Zr and Mg.

[0008] In some embodiments, the method for preparing the aforementioned positive electrode active material includes: (i) mixing a nickel manganese composite hydroxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total amount of metal in the nickel manganese composite hydroxide with a lithium raw material, and performing a first heat treatment to obtain a lithium nickel manganese composite oxide, (ii) adding the obtained lithium nickel manganese composite oxide to a solution of an Al raw material mixed in an aqueous solvent, followed by mixing and drying, and (iii) dry-mixing the obtained product with a Zr raw material and a Mg raw material and performing a second heat treatment to obtain the positive electrode active material.

[0009] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.

[0010] In some embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.

[0011] The positive electrode active material according to some embodiments is prepared by maximizing capacity while minimizing production cost to ensure long cycle life characteristics and improve high voltage characteristics and high temperature characteristics. When the positive electrode active material is applied to a rechargeable lithium battery, a high initial charge / discharge capacity and efficiency can be achieved under high voltage conditions, a long cycle life characteristic can be achieved, and the amount of gas generated due to high voltage and high temperature operation can be effectively suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a schematic diagram schematically illustrating a rechargeable lithium battery according to some embodiments.

[0013] <Description of Reference Numerals>

[0014] 100: Rechargeable lithium battery 10: Positive electrode

[0015] 20: Negative electrode 30: Separator

[0016] 40: electrode assembly 50: shell DETAILED DESCRIPTION

[0017] Hereinafter, specific embodiments will be described in detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.

[0018] The terms used herein are for describing the embodiments only and are not intended to limit the present invention. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.

[0019] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.

[0020] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to indicate the presence of implemented features, quantities, steps, elements or combinations thereof, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements or combinations thereof.

[0021] In the drawings, the thickness of layers, films, panels, regions, etc., is exaggerated for clarity, and the same reference numerals represent the same elements throughout the specification. It will be understood that when an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it can be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In contrast, when an element is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.

[0022] In addition, the "layer" herein includes not only a shape formed on the entire surface but also a shape formed on a part of the surface when viewed from a plan view.

[0023] In addition, the average particle size can be measured by methods well known to those skilled in the art, for example, it can be measured by a particle size analyzer, or it can be measured by a transmission electron microscope image or a scanning electron microscope image. Alternatively, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, when no other definition is provided, the average particle size (D 50 ) means the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image.

[0024] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, A+B, etc.

[0025] The term "metal" is interpreted as a concept including common metals, transition metals and metalloids (semimetals).

[0026] Positive electrode active material

[0027] In some embodiments, the positive electrode active material includes: a core particle, which includes a lithium nickel manganese composite oxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total amount of metals other than lithium in the lithium nickel manganese composite oxide; and a coating disposed on the surface of the core particle and including Al, Zr and Mg.

[0028] Since the price of rare metal cobalt has risen sharply recently, it is necessary to develop positive electrode active materials that exclude cobalt or reduce the cobalt content. Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.) are limited in achieving high capacity due to the small available lithium capacity in the structure. Due to the high available lithium capacity in the structure, the lithium nickel manganese positive electrode active material of the layered structure has excellent capacity and efficiency characteristics, making it suitable as a material for high-capacity batteries. However, as cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In addition, cobalt is excluded, and there is a problem that the side reaction between the positive electrode active material and the electrolyte is accelerated under high voltage and high temperature conditions, which increases the amount of generated gas and deteriorates the cycle life characteristics.

[0029] In some embodiments, a positive electrode active material is provided in which a layered structured lithium nickel manganese composite oxide is used as a core particle and a coating layer including Al, Zr and Mg is introduced to maximize capacity and efficiency while minimizing production costs and reducing the amount of generated gas even under high voltage or high temperature conditions to achieve long cycle life characteristics.

[0030] Nuclear particles

[0031] The core particles include lithium nickel manganese composite oxides, and the nickel content satisfies greater than or equal to about 60 mol% based on the total amount of metals other than lithium in the positive electrode active material of 100 mol%. Nickel is contained in the core particles, but can move to some coatings during the coating process. Therefore, the nickel content may refer to the nickel content contained in the entire positive electrode active material. Based on the total amount of metals other than lithium in the positive electrode active material of 100 mol%, the nickel content may be, for example, about 60 mol% to about 80 mol%, about 65 mol% to about 80 mol%, about 70 mol% to about 80 mol%, about 60 mol% to about 79 mol%, about 60 mol% to about 78 mol% or about 60 mol% to about 75 mol%. If the nickel content meets the above range, even if the cobalt content is reduced, high capacity can be achieved and structural stability can be increased.

[0032] For example, based on 100 mol% of the total amount of metals other than lithium in the lithium nickel manganese composite oxide, the manganese content may be, for example, about 10 mol% to about 40 mol%, such as about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol% or about 20 mol% to about 30%. If the manganese content satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.

[0033] The lithium nickel manganese composite oxide may be, for example, a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. When the lithium nickel manganese composite oxide includes aluminum, it is beneficial to maintain a stable layered structure even if the cobalt element is excluded from the structure. The aluminum content of the lithium nickel manganese aluminum composite oxide based on 100 mol% may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the aluminum content meets the above range, even if cobalt is excluded, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed, and the long cycle life characteristics of the positive electrode active material can be achieved.

[0034] According to some embodiments, the concentration of aluminum in the core particle can be uniform. In other words, it means that there is no concentration gradient of aluminum from the center to the surface in the core particle, or the aluminum concentration of the inner part of the core particle is neither higher than nor lower than the aluminum concentration of the outer part, and the aluminum is uniformly distributed in the core particle. This can be a structure obtained by using an aluminum raw material (hereinafter also referred to as "Al raw material") during the precursor production period, and not additionally doping aluminum during the synthesis period of the core particle, thereby using a nickel-manganese-aluminum composite hydroxide as a precursor to synthesize a composite oxide. The core particle can be in the form of a secondary particle in which a plurality of primary particles are gathered, and the aluminum content inside the primary particle can be the same or similar, regardless of the position of the primary particle. In other words, if the primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content is measured inside the primary particle rather than at its interface, then regardless of the position of the primary particle (that is, regardless of whether the primary particle is close to the center of the secondary particle or close to its surface), the aluminum content can be the same / similar / uniform. In this structure, even if cobalt is absent or present in a very small amount, a stable layered structure can be maintained and aluminum byproducts or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.

[0035] The lithium nickel manganese composite oxide can be specifically represented by Chemical Formula 1.

[0036] [Chemical Formula 1]

[0037] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1

[0038] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.8, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.4, 0 ≤ z1 ≤ 0.03, 0 ≤ w1 ≤ 0.3, 0.9 ≤ x1 + y1 + z1 + w1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

[0039] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. Additionally, Chemical Formula 1 may contain aluminum, in which case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 may be satisfied, and for example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 may be satisfied.

[0040] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.

[0041] The lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, the cobalt content of the lithium nickel manganese composite oxide may be about 0 mol% to about 0.01 mol% based on 100 mol% of the total amount of metals other than lithium in the lithium nickel manganese composite oxide.

[0042] The core particle may be in the form of a secondary particle prepared by aggregating a plurality of primary particles. The secondary particle may be spherical, ellipsoidal, polyhedral or irregular in shape, and the primary particle may be spherical, ellipsoidal, plate-like or a combination thereof.

[0043] When the battery is operated under high voltage or high temperature conditions, the core particles are susceptible to chemical attack by components in the electrolyte, and many side reactions with the electrolyte may occur. Accordingly, there is a problem of reducing the battery cycle life and safety due to the generation of a large amount of gas. According to some embodiments to be described later, these problems can be solved by introducing a coating.

[0044] coating

[0045] In some embodiments, Al, Zr, and Mg are all included in the coating layer, and the amount of gas generated under high voltage or high temperature driving conditions can be significantly reduced, and the cycle life characteristics can be improved compared to the case where any one of Al, Zr, and Mg is excluded. 3+ 、Zr 4+ and Mg 2+ By simultaneously coating three types of metal cations having oxidation states of 2+, 3+, and 4+, the charge balance can be increased and the high voltage characteristics can be improved.

[0046] Based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, the Al content in the coating may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%. This refers only to the content of aluminum included in the coating, which is separate from the aluminum included in the core particles. The aluminum content in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating satisfies these ranges, the coating can have a uniform and thin thickness, which does not increase the resistance of the positive electrode active material, and effectively inhibits side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the aluminum content of the coating is too much, a uniform coating may not be formed or the resistance may increase, which may reduce the charge / discharge efficiency and cycle life characteristics, and if the aluminum content of the coating is too little, a coating of appropriate thickness may not be formed and the effect of suppressing side reactions with the electrolyte may be reduced.

[0047] Based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, the Zr content of the coating may be about 0.1 mol% to about 0.4 mol%, for example, about 0.2 mol% to about 0.4 mol%. In addition, based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, the Mg content of the coating may be about 0.1 mol% to about 0.5 mol%, for example, about 0.1 mol% to about 0.4 mol%. When the Zr content and the Mg content of the coating meet the above ranges, the positive electrode active material forms a good coating without reducing the capacity or increasing the resistance, effectively suppresses the side reaction with the electrolyte, and effectively reduces the amount of gas generated under high voltage or high temperature conditions.

[0048] The ratio of the Zr content and the Mg content to the Al content in the coating may be about 0.06 to about 0.65, for example, about 0.1 to about 0.6, about 0.1 to about 0.5, about 0.1 to about 0.45, about 0.2 to about 0.40, or may be greater than 0.06 and less than about 0.65 (for example, about 0.1 to about 0.65), or greater than 0.06 and less than about 0.45. This means the content ratio of (Zr+Mg) / Al, and the content may mean the molar content. When the content ratio of each element in the coating satisfies the above range, the capacity characteristics and cycle life characteristics at high voltage can be maximized.

[0049] The coating according to some embodiments may be in the form of a film that continuously surrounds the surface of the core particle, for example, it may be in the form of a shell that surrounds the entire surface of the core particle. This is different from a structure in which only a portion of the surface of the core particle is partially coated. According to some embodiments, the coating may be formed to completely cover the surface of the core particle, and may be formed to be very thin and uniform in thickness, so that the positive electrode active material does not increase resistance or reduce capacity, improves structural stability, effectively inhibits side reactions with the electrolyte, reduces the amount of gas generated under high voltage and high temperature conditions, and achieves long cycle life characteristics.

[0050] The thickness of the coating may be about 5 nm to about 500 nm, such as about 5 nm to about 450 nm, about 10 nm to about 400 nm, about 20 nm to about 350 nm, about 30 nm to about 300 nm, about 30 nm to about 250 nm, about 30 nm to about 200 nm, about 30 nm to about 150 nm, about 50 nm to about 500 nm, about 80 nm to about 500 nm, or about 100 nm to about 500 nm. When the thickness of the coating meets these ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed. The thickness of the coating can be measured by, for example, TOF-SIMS, XPS or EDS analysis, and the thickness range of the coating can be measured by TEM-EDS line profile.

[0051] The coating according to some embodiments is characterized by being thin and uniform in thickness, at the level of tens of nanometers to hundreds of nanometers. For example, the deviation of the coating thickness within a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within a positive electrode active material particle. For example, the deviation of the coating thickness can be calculated by measuring the thickness of about 10 points in an electron microscope image of a cross-section of a single positive electrode active material particle to calculate the arithmetic mean, and then dividing the absolute value of the difference between one measurement data and the arithmetic mean by the arithmetic mean and multiplying by 100.

[0052] The fact that the deviation or standard deviation of the coating thickness satisfies the above range means that a coating of uniform thickness is well formed in the form of a film on the surface of the core particles of the positive electrode active material. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed, and the resistance increase or capacity reduction caused by the coating can be minimized.

[0053] Due to the characteristics of each element in the coating, Al may exist in the form of a continuous film, and Zr and Mg may exist in the form of islands.

[0054] In some embodiments, Al, Zr and Mg may each form a separate layer. For example, the positive electrode active material according to some embodiments may include: a first coating layer disposed on the surface of the core particle and including Al, and a second coating layer disposed on the first coating layer and including Zr and Mg. When aluminum is first attached or adsorbed to the surface of the core particle, a first coating layer in the form of a thin film may be formed, and then zirconium and magnesium may be coated thereon to form a second coating layer. Of course, Al, Zr and Mg may be mixed in the first coating layer and the second coating layer, but the first coating layer may be an Al-rich coating layer mainly composed of Al, and the second coating layer may be a Zr / Mg-rich coating layer mainly composed of Zr and Mg.

[0055] The thickness of the first coating and the thickness of the second coating are not particularly limited. However, the thickness of the first coating may be about 1nm to about 200nm, such as about 10nm to about 200nm, about 20nm to about 200nm, or about 30nm to about 180nm. The thickness of the second coating may be about 2nm to about 300nm, such as about 10nm to about 250nm, about 20nm to about 200nm, about 30nm to about 300nm, or about 50nm to about 300nm. When the respective thicknesses meet the above ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the amount of gas generated during high voltage and high temperature operation can be effectively reduced by effectively suppressing the side reaction with the electrolyte.

[0056] Meanwhile, in addition to Al, Zr and Mg, the coating may further include nickel, manganese or a combination thereof. The nickel and manganese included in the core particles may be introduced during the coating formation process, and their contents are not particularly limited. The coating according to some embodiments substantially includes Al, Zr and Mg, and optionally includes nickel and manganese, and is formed to be thin and uniform in thickness, thereby improving the high voltage characteristics of the positive electrode active material and improving the cycle life characteristics.

[0057] Grain boundary coating part

[0058] During the coating formation process, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to some embodiments may further include a grain boundary coating portion, which includes aluminum and is disposed on the surface of the primary particles in the inner portion of the secondary particles. In this article, the secondary particle refers to the core particle, and the inner portion of the secondary particle may mean the entire inner portion except the surface of the secondary particle, or may be a zone of about 60% of the radius of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle) from the center of the secondary particle to the surface of the secondary particle. The grain boundary coating is a different concept from the coating on the surface of the core particle, and refers to the coating portion formed on the surface of the primary particle inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming an aluminum grain boundary coating portion, the positive electrode active material can become more structurally stable, and its cycle life characteristics can be improved.

[0059] The aluminum content in the grain boundary coating portion is not particularly limited, and for example, the aluminum content in the grain boundary coating portion may be smaller than the aluminum content in the coating layer.

[0060] The grain boundary coating portion may further include magnesium in addition to aluminum. In addition, the grain boundary coating portion may further include nickel, manganese, or a combination thereof.

[0061] According to some embodiments, the average particle size (D 50 ) is not particularly limited, but may be, for example, about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm. As used herein, when no limitation is otherwise provided, the average particle size (D 50 ) means the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of the positive electrode active material. When the average particle size of the positive electrode active material satisfies the above range, high capacity and long cycle life can be achieved, and it can be beneficial to form a coating according to some embodiments.

[0062] The cobalt content in the positive electrode active material according to some embodiments may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, for example, about 0 mol% to about 0.01 mol%, based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material. The positive electrode active material according to some embodiments may be, for example, a cobalt-free positive electrode active material.

[0063] In addition, in some embodiments, another positive electrode active material may be characterized as not including sodium. Generally speaking, sodium ions can be used in the preparation process of the positive electrode active material, but according to the preparation method described later, core particles having a stable structure and a coating layer of uniform thickness can be formed without using sodium ions.

[0064] Method for preparing positive electrode active material

[0065] In some embodiments, a method for preparing a positive electrode active material includes: (i) mixing a nickel manganese composite hydroxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total amount of metal in the nickel manganese composite hydroxide with a lithium raw material, and performing a first heat treatment to obtain a lithium nickel manganese composite oxide, (ii) adding the obtained lithium nickel manganese composite oxide to a solution of an Al raw material mixed in an aqueous solvent, followed by mixing and drying, and (iii) dry-mixing the obtained product with a Zr raw material and a Mg raw material, and performing a second heat treatment to obtain the positive electrode active material.

[0066] The nickel-manganese composite hydroxide may not include cobalt or may include a very small amount of cobalt, and may be, for example, a cobalt-free nickel-manganese composite hydroxide. For example, it may be a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese composite hydroxide may be prepared by a general coprecipitation method.

[0067] Based on the total amount of 100mol% of metal in the nickel-manganese composite hydroxide, the nickel content in the nickel-manganese composite hydroxide may be greater than or equal to about 60mol%, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. When the nickel content meets the above range, even if the cobalt content is reduced, high capacity can be achieved and structural stability can be increased.

[0068] The manganese content in the nickel-manganese-based composite hydroxide may be about 10 mol% to about 40 mol%, about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30 mol%, based on 100 mol% of the total amount of metal in the nickel-manganese-based composite hydroxide.

[0069] In addition, based on the total amount of 100mol% of metal in the nickel-manganese composite hydroxide, when the nickel-manganese composite hydroxide further contains aluminum, the aluminum content may be greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol%, or greater than or equal to about 1mol%, for example, about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol%, or about 1mol% to about 1.9mol%. When the manganese content and aluminum content of the nickel-manganese composite hydroxide meet the above range, high capacity can be achieved, the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.

[0070] In the nickel-manganese composite hydroxide, the cobalt content may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on 100 mol% of the total amount of metal. The nickel-manganese composite hydroxide may be economical because it avoids the increase in unit cost caused by cobalt, maximizes capacity, and improves structural stability.

[0071] As an example, the nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.

[0072] [Chemical formula 2]

[0073] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2

[0074] In Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.

[0075] In Chemical Formula 2, for example, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.

[0076] The nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) may be about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm.

[0077] In the preparation process of the core particles, aluminum is additionally doped on the core particles, but an aluminum raw material is used to prepare a precursor of a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed in the structure. This precursor can be used to prepare a positive electrode active material that can stably maintain a layered structure without cobalt despite repeated charging and discharging, in which aluminum byproducts or aluminum aggregates are not formed, and as a result, the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material are improved.

[0078] The nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2. The first heat treatment can be carried out in an oxygen atmosphere, for example, in a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel-manganese composite oxide can be obtained. Based on the total amount of 100mol% of the metal in the obtained lithium nickel-manganese composite oxide, the obtained lithium nickel-manganese composite oxide may include about 60mol% or more, for example, about 60mol% to about 80mol% of nickel, but may not include cobalt or include a very small amount of cobalt less than or equal to about 0.01mol%.

[0079] The lithium nickel manganese composite oxide has a significantly different residual lithium content and different surface characteristics from oxides having other compositions (e.g., conventional nickel oxides, such as lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, etc.), and conventional coating methods may not be able to successfully form a good coating in the form of a uniform film thereon. In some embodiments, such a method (by uniformly forming a coating with a very thin thickness on the surface of a lithium nickel manganese composite oxide having a very small amount of cobalt and a nickel content of greater than or equal to about 60 mol%) is applied to improve high voltage characteristics.

[0080] In some embodiments, the Al coating is performed by adding the lithium nickel manganese based composite oxide obtained by the first heat treatment to an aqueous solvent mixed with an aluminum raw material, followed by drying and the second heat treatment, and performing Al coating in a wet method.

[0081] The aqueous solvent may include distilled water, an alcohol solvent or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof. For example, the aluminum raw material may include aluminum sulfate, and in this case, it is beneficial to form a coating having a uniform thickness on the surface of the lithium nickel manganese composite oxide particles.

[0082] The aluminum raw material is a raw material for forming a coating layer, and the aluminum content in the aluminum raw material can be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material finally obtained. If the Al content in the coating layer is designed to have this range, the coating layer can be formed to have a thin and uniform thickness of tens or hundreds of nanometers, which can reduce the amount of gas generated by the rechargeable lithium battery under high voltage or high temperature operating conditions, and improve high capacity and long cycle life characteristics.

[0083] The solution obtained by mixing the aluminum raw material in an aqueous solvent may have a pH of about 1.5 to about 3.5, for example, about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2. The lithium nickel manganese composite oxide is added dropwise and mixed into an aqueous solvent mixed with the aluminum raw material for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, for example, about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. When these conditions are met, it is beneficial to form a coating with a uniform thickness.

[0084] Drying after the mixing process may be understood as a process of removing the solvent, and may be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C.

[0085] The second heat treatment can be understood as a process for forming an Al / Zr / Mg coating, and can be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 to about 10 hours. In addition, the second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time can be the same as the first heat treatment time or shorter than the first heat treatment time. The desired coating can be obtained by performing the second heat treatment under these conditions.

[0086] Based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, the Zr content in the Zr raw material can be designed to be about 0.1 mol% to about 0.4 mol% or about 0.2 mol% to about 0.4 mol%. In addition, based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, the Mg content in the Mg raw material can be designed to be about 0.1 mol% to about 0.5 mol% or about 0.1 mol% to about 0.4 mol%.

[0087] The Zr raw material may include, for example, zirconium oxide, zirconium silicate, or a combination thereof. The Mg raw material may include, for example, magnesium oxide, magnesium phosphate, magnesium carbonate, or a combination thereof.

[0088] Positive electrode

[0089] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof.

[0090] According to some embodiments, the loading level of the positive electrode active material layer may be about 5 mg / cm 2 ~ about 40mg / cm 2 , for example about 5 mg / cm 2 ~about 30mg / cm 2 , about 10mg / cm 2 ~about 20mg / cm 2 or about 5 mg / cm 2 -~about 15mg / cm 2 .

[0091] In addition, the density of the positive electrode active material layer in the final pressed positive electrode can be about 3.3 g / cc to about 3.7 g / cc, such as about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. When applying the positive electrode active material according to some embodiments, it is advantageous to implement such a loading level and positive electrode density, and the positive electrode satisfying the loading level and positive electrode density within the above range is suitable for implementing a high capacity, high energy density rechargeable lithium battery.

[0092] Binder

[0093] The binder improves the bonding properties between the positive electrode active material particles and the bonding properties between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin or nylon, but are not limited thereto.

[0094] Conductive Materials

[0095] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0096] Each of the binder and the conductive material may be included in an amount of about 0 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer.

[0097] The positive electrode current collector may include Al foil, but is not limited thereto.

[0098] Rechargeable lithium battery

[0099] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, negative electrode, and electrolyte.

[0100] Rechargeable lithium batteries may be classified into cylindrical batteries, prismatic batteries, pouch-type batteries, coin-type batteries, etc. according to shapes. Figure 1 Schematic diagram showing a rechargeable lithium battery according to some embodiments. Figure 1 , the rechargeable lithium battery 100 includes: an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50, the electrode assembly 40 being accommodated in the case 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).

[0101] The rechargeable lithium battery according to some embodiments may be rechargeable at a high voltage, or may be suitable for being driven at a high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long cycle life characteristics.

[0102] Negative electrode

[0103] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material, or a combination thereof.

[0104] Negative electrode active material

[0105] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / de-doping lithium, or a transition metal oxide.

[0106] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbon-based negative electrode active material. The crystalline carbon may be natural graphite or artificial graphite in an amorphous or flaky, lamellar, spherical, or fibrous form. The amorphous carbon may be soft carbon, hard carbon, a mesophase pitch carbonized product, calcined coke, etc.

[0107] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0108] The material capable of doping / de-doping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof) or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO2, a Sn alloy, SnO x (0 < x < 2) or a combination thereof.

[0109] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include secondary particles (cores) in which silicon primary particles are assembled and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon may also be present between the silicon primary particles. For example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0110] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include: a core including crystalline carbon and silicon particles, and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonization products, and calcined coke.

[0111] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content of silicon may be about 10 wt% to about 50 wt%, and the content of amorphous carbon may be about 50 wt% to about 90 wt%. Additionally, when the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content of silicon may be about 10 wt% to about 50 wt%, the content of crystalline carbon may be about 10 wt% to about 70 wt%, and the content of amorphous carbon may be about 20 wt% to about 40 wt%.

[0112] Additionally, the thickness of the amorphous carbon coating may be about 5 nm to about 100 nm. The average particle size (D 50 ) of the silicon particles (primary particles) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist alone as silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0 < x ≤ 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation may be about 99:1 to about 33:67. As used herein, when not otherwise limited, the average particle size (D 50 ) indicates the diameter of the particles in the particle distribution with a cumulative volume of about 50% by volume.

[0113] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be a weight ratio of about 1:99 to about 90:10.

[0114] Binder

[0115] The binder is used to bond the negative electrode active material particles to each other well and is also used to bond the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0116] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0117] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol or a combination thereof.

[0118] When an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K or Li.

[0119] The dry binder may be a polymer material that can be turned into fibers, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0120] Conductive Materials

[0121] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0122] Based on 100wt% of the negative electrode active material layer, the content of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0.5wt% to about 5wt% of the conductive material.

[0123] Negative electrode current collector

[0124] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm or about 7 μm to about 10 μm.

[0125] Electrolyte

[0126] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.

[0127] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.

[0128] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In addition, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.

[0129] The nonaqueous organic solvent may be used alone or in a mixture of two or more types, and when the nonaqueous organic solvent is used in a mixture of two or more types, the mixing ratio may be appropriately adjusted according to desired battery performance, which is well known to those skilled in the art.

[0130] When the carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.

[0131] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.

[0132] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate or ethylene carbonate-based compounds to improve the battery cycle life.

[0133] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0134] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).

[0135] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate ion conductivity and viscosity, and thus excellent performance may be achieved, and lithium ions may be efficiently moved.

[0136] Diaphragm

[0137] Depending on the type of rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0138] The separator may include a porous substrate and a coating on one or both (eg, two opposite) surfaces of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.

[0139] The porous substrate may be a polymer film formed by any one polymer selected from polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon), or copolymers or mixtures of two or more thereof.

[0140] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0141] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.

[0142] The inorganic material may include inorganic particles selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.

[0143] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0144] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.

[0145] Examples and comparative examples of the present disclosure are described below. However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.

[0146] Example 1

[0147] 1. Preparation of positive electrode active material

[0148] Ni 0.75 Mn 0.23 Al 0.02(OH)2 and LiOH were mixed in a molar ratio of 1:1.05 and then subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to prepare a Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 14 μm (D 50 ) in the form of secondary particles.

[0149] After aluminum sulfate is mixed with a distilled water solvent, a composite oxide is added thereto and then mixed for 20 to 60 minutes. In this article, the aluminum content in aluminum sulfate is designed to be 1.0 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material. After removing the solvent from the mixed solution and then drying the remainder at 190 ° C, zirconium oxide powder and magnesium oxide powder are dry mixed with it, and then a second heat treatment is performed at 825 ° C for 8 hours under an oxygen atmosphere to obtain the final positive electrode active material. In this article, the zirconium content in zirconium oxide is designed to be 0.2 mol% based on 100 mol% of the total amount of metals other than lithium in the final positive electrode active material, and the magnesium content in magnesium oxide is designed to be 0.1 mol% based on 100 mol% of the total amount of metals other than lithium in the final positive electrode active material.

[0150] 2. Preparation of rechargeable lithium battery cells

[0151] Based on the total weight of the positive electrode active material layer slurry, 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material were mixed to prepare the positive electrode active material layer slurry, and the slurry was coated on an aluminum foil positive electrode current collector, and then dried and pressed to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10mg / cm 2 , and the density of the positive electrode active material layer in the final rolled positive electrode was about 3.4 g / cc.

[0152] Based on the total weight of the negative electrode active material layer slurry, 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene-butadiene rubber were mixed in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil negative electrode current collector, and then dried and pressed to prepare a negative electrode.

[0153] A rechargeable lithium battery cell was prepared in a conventional method using a polytetrafluoroethylene separator and using an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0154] Example 2

[0155] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the magnesium content in magnesium oxide was designed to be 0.2 mol % based on 100 mol % of the total amount of metals other than lithium in the final positive electrode active material.

[0156] Example 3

[0157] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the magnesium content in magnesium oxide was designed to be 0.4 mol % based on 100 mol % of the total amount of metals other than lithium in the final positive electrode active material.

[0158] Example 4

[0159] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 2, except that the zirconium content in zirconium oxide was designed to be 0.4 mol % based on 100 mol % of the total amount of metals other than lithium in the final positive electrode active material.

[0160] Comparative Example 1

[0161] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that a positive electrode active material without a Mg coating layer was prepared by not adding magnesium oxide powder.

[0162] Comparative Example 2

[0163] The positive electrode active material was prepared in substantially the same manner as in Example 1, except that the coating of Zr and Mg was omitted by dry coating of aluminum. 1.05 Ni 0.75 Mn 0.23 Al 0.02 A composite oxide in the form of secondary particles of a composition of O2 was mixed with alumina powder and then heat-treated at 825°C for 8 hours under an oxygen atmosphere to prepare a positive electrode active material dry-coated with Al. A rechargeable lithium battery cell was prepared in substantially the same manner as in Example 1 except that it was used as a positive electrode active material.

[0164] Comparative Example 3

[0165] Ni 0.75 Mn 0.25(OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and then subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to prepare a molten-silicon-based composite having an average particle size (D 50 ) is a composite oxide doped with aluminum in the form of secondary particles of about 14 μm. The composite oxide doped with aluminum is mixed with aluminum oxide powder and then subjected to a second heat treatment at 825° C. for 8 hours under an oxygen atmosphere to prepare an Al-coated positive electrode active material. A rechargeable lithium battery cell is prepared in substantially the same manner as Example 1 except that it is used as a positive electrode active material.

[0166] Comparative Example 4

[0167] Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat treated at 850°C for 8 hours in an oxygen atmosphere to prepare 50 ) is a composite oxide doped with aluminum in the form of secondary particles of about 14 μm. A rechargeable lithium battery cell was prepared in substantially the same manner as in Example 1 except that it was used as a positive electrode active material.

[0168] Comparative Example 5

[0169] Ni 0.75 Mn 0.25 (OH)2 and LiOH were used in a molar ratio of 1:1 and heat treated at 850 °C for 8 h under an oxygen atmosphere to prepare LiNi 0.75 Mn 0.25 The composition and average particle size of O2 50 ) is a composite oxide in the form of secondary particles of about 14 μm. A rechargeable lithium battery cell was prepared in substantially the same manner as in Example 1, except that it was used as a positive electrode active material.

[0170] For better understanding, the designs of the positive electrode active materials of Examples and Comparative Examples are briefly shown in Table 1.

[0171] (Table 1)

[0172]

[0173]

[0174] Evaluation Example 1: Evaluation of initial charge / discharge capacity and efficiency

[0175] The rechargeable lithium battery cells according to Examples 1 to 4 and Comparative Examples 1 to 5 were constant current charged to 4.45V at 0.2C and constant voltage charged to 0.05C, and then discharged to a cut-off voltage of 3.0V at 0.2C at 25°C as initial charge and discharge. Table 1 shows the initial charge capacity, the initial discharge capacity, and the ratio of the initial discharge capacity to the initial charge capacity as efficiency.

[0176] Evaluation Example 2: Cycle Life Characteristics

[0177] After the initial charge and discharge of Evaluation Example 1, each battery cell was repeatedly charged and discharged 25 times at 1.0C in the voltage range of 3.0V to 4.45V to calculate the ratio of the 25th discharge capacity to the initial discharge capacity (ie, cycle life), and the results are shown in Table 1.

[0178] Evaluation Example 3: Evaluation of the amount of generated gas

[0179] The battery cells of Example 2 and Comparative Examples 1 to 5 were initially charged at 4.45 V as in Evaluation Example 1 and stored at 90° C. for 4 hours to measure the amount of generated gas, and the results are shown in Table 1.

[0180] Referring to Table 1, Examples 1 to 4 exhibit improved cycle-life characteristics while maintaining high initial charge capacity and initial discharge capacity and efficiency under high voltage conditions, and Example 2 exhibits significantly reduced amount of generated gas under high voltage conditions.

[0181] Compared with the embodiment, Comparative Example 1 in which the coating of Mg is omitted exhibits slightly reduced cycle life characteristics at high voltage and generates a larger amount of gas at high temperature. Comparative Example 2 in which Al is dry coated and Zr and Mg coatings are omitted exhibits significantly deteriorated cycle life characteristics at high voltage, and the amount of gas generated at high temperature is also greater than that of the embodiment. Comparative Example 3 in which core particles are synthesized by dry coating Al alone and doping aluminum and omitting Zr and Mg coatings exhibits significantly deteriorated initial discharge capacity and charge / discharge efficiency at high voltage, significantly low cycle life characteristics, and a high amount of gas generated at high temperature. Comparative Example 4 in which core particles are synthesized by doping Al alone and omitting Al, Zr and Mg coatings exhibits deteriorated cycle life characteristics at high voltage, and the amount of gas generated at high temperature is very high. Comparative Example 5 in which Al is not introduced into the core particles in the case of omitting Al, Zr and Mg coatings exhibits significantly deteriorated cycle life characteristics at high voltage, and the amount of gas generated at high temperature is too high, so that it cannot be used commercially.

[0182] Although the present invention has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present invention should not be limited to the disclosed embodiments, but rather is intended to cover one or more suitable various modifications and equivalent arrangements included within the spirit and scope of the claims.

Claims

1. A positive electrode active material comprising: a core particle including a lithium nickel manganese-based composite oxide having a nickel content of 60 mol% or more based on 100 mol% of the total amount of metals other than lithium in the lithium nickel manganese-based composite oxide, and A coating layer is disposed on the surface of the core particle and includes Al, Zr, and Mg.

2. The positive electrode active material according to claim 1, wherein The coating has an Al content of 0.1 mol% to 2 mol%, a Zr content of 0.1 mol% to 0.4 mol%, and a Mg content of 0.1 mol% to 0.5 mol%, based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material.

3. The positive electrode active material according to claim 1, wherein The ratio of the Zr content and the Mg content to the Al content in the coating is 0.1 to 0.

65.

4. The positive electrode active material according to claim 1, wherein The coating is in the form of a shell that continuously surrounds the surface of the core particle.

5. The positive electrode active material according to claim 1, wherein The coating has a thickness of 5 nm to 500 nm.

6. The positive electrode active material according to claim 1, wherein The coating further includes nickel, manganese, or a combination thereof.

7. The positive electrode active material according to claim 1, wherein The lithium nickel manganese-based composite oxide of the core particle has a nickel content of 60 mol % to 80 mol % based on 100 mol % of the total amount of metals other than lithium in the positive electrode active material.

8. The positive electrode active material according to claim 1, wherein The lithium nickel manganese-based composite oxide of the core particle is a lithium nickel manganese aluminum-based composite oxide further including aluminum in addition to nickel and manganese, and The content of aluminum in the lithium nickel manganese aluminum-based composite oxide is 1 mol % to 3 mol % based on 100 mol % of the total amount of metals other than lithium in the lithium nickel manganese aluminum-based composite oxide.

9. The positive electrode active material according to claim 1, wherein The lithium nickel manganese-based composite oxide of the core particle is represented by Chemical Formula 1: [Chemical formula 1] Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 in, In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.

10. The positive electrode active material according to claim 9, wherein In Chemical Formula 1, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, and 0≤w1≤0.

29.

11. The positive electrode active material according to claim 1, wherein The cobalt content is 0 mol % to 0.01 mol % based on 100 mol % of the total amount of metals other than lithium in the positive electrode active material.

12. The positive electrode active material according to claim 1, wherein The core particle is in the form of a secondary particle prepared by aggregating a plurality of primary particles.

13. The positive electrode active material according to claim 12, wherein The positive electrode active material further includes a grain boundary coating portion including Al and provided on a surface of the primary particle in an inner portion of the secondary particle.

14. The positive electrode active material according to claim 13, wherein The Al content of the grain boundary coating portion is less than the Al content in the coating layer.

15. The positive electrode active material according to claim 13, wherein The grain boundary coating portion further includes Mg.

16. The positive electrode active material according to claim 1, wherein The positive electrode active material has an average particle size of 10 μm to 18 μm.

17. The positive electrode active material according to claim 1, wherein The positive electrode active material does not include sodium.

18. A method for preparing a positive electrode active material, comprising: mixing a nickel-manganese-based composite hydroxide having a nickel content of 60 mol% or more based on 100 mol% of the total amount of metals in the nickel-manganese-based composite hydroxide with a lithium raw material, and performing a first heat treatment to obtain a lithium nickel-manganese-based composite oxide, adding the obtained lithium nickel manganese-based composite oxide to a solution of an Al raw material mixed in an aqueous solvent, followed by mixing and drying, and The obtained product was dry-mixed with a Zr raw material and a Mg raw material, and subjected to a second heat treatment to obtain a positive electrode active material.

19. The method of claim 18, wherein The Al content in the Al raw material is 0.1 mol% to 2 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material. The Zr content in the Zr raw material is 0.1 mol% to 0.4 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material, and The Mg content in the Mg raw material is 0.1 mol% to 0.5 mol% based on 100 mol% of the total amount of metals other than lithium in the positive electrode active material.

20. The method of claim 18, wherein The Al raw material includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof. The Zr raw material includes zirconium oxide, zirconium silicate or a combination thereof, and The Mg raw material includes magnesium oxide, magnesium phosphate, magnesium carbonate or a combination thereof.

21. The method of claim 18, wherein The pH of the solution of the Al raw material mixed in the aqueous solvent is 1.5 to 3.

5.

22. The method of claim 18, wherein The first heat treatment is performed at 750°C to 950°C, and The second heat treatment is performed at 700°C to 850°C.

23. The method of claim 18, wherein The nickel-manganese-based composite hydroxide is a nickel-manganese-aluminum-based composite hydroxide further including aluminum, and the aluminum content in the nickel-manganese-aluminum-based composite hydroxide is 1 mol% to 3 mol% based on 100 mol% of the total amount of metals in the nickel-manganese-aluminum-based composite hydroxide.

24. A positive electrode comprising a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 17 or the positive electrode active material prepared by the method according to any one of claims 18 to 23.

25. A rechargeable lithium battery comprising The positive electrode according to claim 24, negative electrode, and Electrolyte.

26. The rechargeable lithium battery of claim 25, wherein The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.

Citation Information

Patent Citations

  • Power module and manufacturing method thereof

    KR1020230101766A